DRIBBLING FUTSAL TRAINING MODEL BASED ON GAME FOR SENIOR HIGH SCHOOL - Achmad Alfi Suryanata; Ramdan Pelana; Yasep Setiakarnawijaya (Gladi : Jurnal Ilmu Keolahragaan, 2021)
The goal to be achieved from this research and development is to produce a model of gameplay futsal dribbling skill-based skill training for senior high school. This research and development are conducted to get information about the development and implementation of the model of game-based futsal dribbling skill training for senior high school and to know the effectiveness of the resulting model. This research uses Research & Development (R & D) method from ADDIE. Subjects in this study were senior high school students who followed extracurricular futsal consisting of 60 children. The steps in this study are: analysis of the product to be created, designing the initial product description, developing a product framework that has been designed, implementing products that have been made with expert validation tests and testing them in large groups, and finally evaluating and testing the effectiveness of the product. The model effectiveness test uses the futsal dribbling skill test which is used to know the level of dribbling ability of the child before and after the treatment of the dribbling skill training model developed. Preliminary tests performed obtained level of dribbling ability of students is 11.3. After given treatment dribbling exercise model obtained the level of dribbling ability of students 10.1. On the significant test the difference with spss 20 obtained mean = 1.16217 shows the difference of pre-test results and post-test results, t-hitung = 18.666 df = 59 and p-value = 0.00 <0.05 which means there is a significant difference between before and after being given a modeling practice of skill futsal dribbling. This model of game-based futsal dribbling skills training for senior high school is effective for improving futsal dribbling skills for senior high school.